Fixism and conservation science. Issue 4 (20th February 2017) - Robert, Alexandre; Fontaine, Colin; Veron, Simon; Monnet, Anne‐Christine; Legrand, Marine; Clavel, Joanne; Chantepie, Stéphane; Couvet, Denis; Ducarme, Frédéric; Fontaine, Benoît; Jiguet, Frédéric; le Viol, Isabelle; et al.
Abstract: The field of biodiversity conservation has recently been criticized as relying on a fixist view of the living world in which existing species constitute at the same time targets of conservation efforts and static states of reference, which is in apparent disagreement with evolutionary dynamics. We reviewed the prominent role of species as conservation units and the common benchmark approach to conservation that aims to use past biodiversity as a reference to conserve current biodiversity. We found that the species approach is justified by the discrepancy between the time scales of macroevolution and human influence and that biodiversity benchmarks are based on reference processes rather than fixed reference states. Overall, we argue that the ethical and theoretical frameworks underlying conservation research are based on macroevolutionary processes, such as extinction dynamics. Current species, phylogenetic, community, and functional conservation approaches constitute short‐term responses to short‐term human effects on these reference processes, and these approaches are consistent with evolutionary principles.